Initiation of renal replacement therapy: is timing everything? - Bouman, Catherine SC (BioMed Central, 2010)
Acute kidney injury is commonly encountered and in the critically ill treatment is principally supportive. A recent large, multicentre study has used retrospective analysis to try and identify patient outcomes when commencing renal replacement therapy using conventional biochemical and physiological markers. The authors have also made an attempt to decipher when to commence renal replacement therapy.